Surveillance of aetiologies, clinical presentation, and most common types of epilepsy among paediatric patients at a tertiary care hospital in Pakistan - Ayesha Nasir Hameed; Muhammad Talha Nawaz; Malik Muhammad Hamza Khan; Hasan Tauqeer; Meher Angez; Malik Muhammad Nazir Khan; admin (Journal of the Pakistan Medical Association, 2023)
Epilepsy is the third most common neurological disease in the world associated with a high incidence in the paediatric age group. This study aims to evaluate the prevalence, types and aetiologies of epilepsy within the Pakistani population. A retrospective review of the charts of all patients, below the age of 18 years, presenting with epilepsy to the Department of Neurology at The Children’s Hospital and Institute of Child Health, Lahore, from January 2016 to December 2020, was carried out. Analysis was performed using SPSS Version 26. A p value of <0.05 was considered statistically significant. A total of 1,097 patients were studied, of which 644 (58.8%) were males and 451 (41.2%) females. a vast majority, i.e. 1,021 (96.1%), of the study participants, belonged to the province of Punjab. Afebrile seizures [n=798 (72.7%)] were more commonly reported than febrile seizures [n=299 (27.3%)]. —Continue